Environmental awareness of Protestant youth in Germany: Perspectives from an empirical exploration - Kroeck, Thomas (HTS teologiese studies, 2021)
Climate change and environmental degradation are pressing issues in the 21st century, which have also been addressed by Christian churches. Christian congregations are expected to provide an important impetus towards a more sustainable way of life. However, in Germany, empirical data on how Christian congregations and their members relate to this issue are scarce. This article presents the first results of a quantitative study on this topic, in particular, with regard to the differences between age groups. The focus is on the perceived importance of environmental conservation, environmental awareness, and the opportunities and obstacles for the engagement of Christians in creation care. An online survey which was conducted in 2020 yielded 736 complete responses from members of the Protestant churches, 19.7% of which were from young people under 30 years. Regarding the perceived importance of environmental conservation and environmental awareness, the results were largely consistent with the data of a representative study on environmental awareness in Germany. The young generation showed slightly lower values than the older ones. Members of Protestant church seem to be more willing to behave sustainably than the general public, with the under 30 years old being in particular concerned about food consumption. Motivational and subcultural opportunities for Christian conservation efforts were identified. Obstacles were based primarily on eschatological views and the fear that other mandates of the church may be neglected. Regarding obstacles, young respondents showed a stronger approval than the older generations.Contribution: The article presents empirical evidence on the environmental awareness of Protestant Christians in Germany and identifies the opportunities and obstacles for their engagement in creation care.